ANALYSIS OF ANTHROPOMETRIC METADATA IN RELATION TO CARDIOPULMONARY RESUSCITATION QUALITY - Filho, Ilamar José Fernandes; Thiago, Isabela Marques; Fontoura, Humberto de Sousa (CIPEEX, 2025)
Widespread training of the population in cardiopulmonary resuscitation (CPR) techniques is of fundamental importance for reducing deaths from cardiac arrest (CA). However, the dissemination of high-quality CPR is still underdeveloped in Brazil. The present study aims to compare the quality of CPR maneuvers by comparing them with the metadata of each participant (age, sex, height, weight, BMI) in the Medicine course through the assembly of a data collection and analysis instrument. The population in question consisted of students from Unievangélica (Universidade Evangélica Goiás), totaling 116 participants from three different semesters. To this end, a cross-sectional analytical study was conducted. Participants reported their anthropometric data and performed the maneuver on a CPR manikin, which was evaluated by a sensor attached to it. The results show that there is a significant influence of the participant’s weight and gender on the quality of the maneuver’s execution. Academic research found results consistent with these. Thus, it is concluded that CPR training is necessary to minimize the interference of anthropometric data so that everyone can perform the maneuver equally well.